1996
DOI: 10.5271/sjweh.104
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors of cancer among men and women in Norwegian agriculture

Abstract: C O~C~U S~O~SThe results support the hypothesis of a relationship between acute leukemia and animal contact and between multiple myeloma and pesticides in potato cultivation. Other exposure associations, especially for cancer among women, warrant further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
66
2

Year Published

1997
1997
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(75 citation statements)
references
References 37 publications
7
66
2
Order By: Relevance
“…The current study confirms that lifestyle-mediated cancers are in deficit in the farming community (9,22).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The current study confirms that lifestyle-mediated cancers are in deficit in the farming community (9,22).…”
Section: Discussionsupporting
confidence: 85%
“…Increased cancer of the eye has been reported for rural populations, and is thought to be related to exposure from sunlight (22,35). In our study, mortality from eye cancer was significantly increased for women (but not men) in region three.…”
Section: Discussionsupporting
confidence: 45%
“…134 There was no increased risk of NHL in a Norwegian cohort study that used pesticides purchased in 1969 as an exposure indicator of pesticide use. 72 In a mortality study in northern Italy of rice growers, 4 cases of NHL were observed (1.18 expected) among growers with 20 or more years of exposure. 70 Chiu et al, 52 using pooled data based on direct interviews from 3 Midwestern case-control studies, 81,82 reported odds ratios between 1.0 and 1.1 for farmers who used herbicides, fungicides, crop insecticides, or animal insecticides.…”
Section: Occupational and Environmental Factors Occupational And Envimentioning
confidence: 99%
“…We linked the file of fasmers and spouses to the Medical Birth Register of Norway to identify their births. The establishment of the cohort and linking procedures have been described in more detail elsewhere (13)(14)(15)(16). On the basis of these linking procedures we established 6 analysis files: a file of mothers (late-term abortion study), their newborn sons (hypospadias and cryptorchidism), female farmers (cancer), male farmers (cancer), farmers' daughters (cancer), and farmers' sons (cancer).…”
Section: Maberiial and Methodsmentioning
confidence: 99%
“…Thus the oldest farmers were 70 years old and the oldest children were 43 years old at the end of the follow-up. In an attempt to avoid bias from a selective loss of unidentified dead children or spouses in the population register (14,15) …”
Section: Reproductive Outcomesmentioning
confidence: 99%